2010
DOI: 10.3402/jom.v2i0.5070
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of periopathogens on host protease inhibitors SLPI, elafin, SCCA1, and SCCA2

Abstract: ObjectiveSecretory leukocyte peptidase inhibitors (SLPI), elafin, squamous cell carcinoma antigen 1 and 2 (SCCA1 and SCCA2) are specific endogenous serine protease inhibitors expressed by epithelial cells that prevent tissue damage from excessive proteolytic enzyme activity due to inflammation. To determine the effects of various periopathogens on these protease inhibitors, we utilized human gingival epithelial cells (GECs) challenged with cell-free bacteria supernatants of various periopathogens Porphyromonas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
33
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 68 publications
7
33
0
3
Order By: Relevance
“…A protective effect of these protease inhibitors in gingival health is shown by our study that demonstrated pre-treatment of GECs with SLPI, SCCA1 or SCCA2 partially attenuated antimicrobial proteins hBD-2 and CCL20 mRNA expression in response to P. gingivalis (Yin, Swanson et al 2010). However, the same study showed the presence of P. gingivalis disrupted the function of these serine protease inhibitors, suggesting that the presence of an organism colonizing oral plaque prior to the establishment by pathogens enhances expression of protease inhibitors that protect GECs, while P. gingivalis secretes proteases that degrade cellular protease inhibitors (Yin, Swanson et al 2010). It is of interest to note that various periodontal pathogens which secrete proteases (P. gingivalis, T. forsythia, A. actinomycetemcomitans) were tested, but P. gingivalis was most effective at degrading protease inhibitors (Figure 2) (Yin, Swanson et al 2010).…”
Section: Regulation Of Protease Inhibitors By Periodontal Pathogensmentioning
confidence: 55%
See 4 more Smart Citations
“…A protective effect of these protease inhibitors in gingival health is shown by our study that demonstrated pre-treatment of GECs with SLPI, SCCA1 or SCCA2 partially attenuated antimicrobial proteins hBD-2 and CCL20 mRNA expression in response to P. gingivalis (Yin, Swanson et al 2010). However, the same study showed the presence of P. gingivalis disrupted the function of these serine protease inhibitors, suggesting that the presence of an organism colonizing oral plaque prior to the establishment by pathogens enhances expression of protease inhibitors that protect GECs, while P. gingivalis secretes proteases that degrade cellular protease inhibitors (Yin, Swanson et al 2010). It is of interest to note that various periodontal pathogens which secrete proteases (P. gingivalis, T. forsythia, A. actinomycetemcomitans) were tested, but P. gingivalis was most effective at degrading protease inhibitors (Figure 2) (Yin, Swanson et al 2010).…”
Section: Regulation Of Protease Inhibitors By Periodontal Pathogensmentioning
confidence: 55%
“…P. gingivalis gingipains have shown to degrade extracellular matrix components such as laminin, fibronectin, and collagen type III, IV, and V in vitro (Potempa, Banbula et al 2000), and are thought to account for at least 85% of the general proteolytic activity displayed by P. gingivalis (Imamura 2003). Our previous in vitro study found that the secretion of SLPI and ELAFIN was significantly reduced in response to P. gingivalis and that P. gingivalis supernatants digested recombinant SLPI, ELAFIN, SCCA1 and 2 (Figure 2) (Yin, Swanson et al 2010). These data suggest degradation of protease inhibitors by P. gingivalis may result in decreased host protective capacity and higher susceptibility to P. gingivalis infection (Yin, Swanson et al 2010).…”
Section: Changes In Protease Inhibitor Levels In Periodontitismentioning
confidence: 92%
See 3 more Smart Citations